Honduras : Report on Observance of Standards and Codes-Fiscal Transparency Module; Update. (IMF Staff Country Reports; Country Report ;, 2005)
Honduras's Report on the Observance of Standards and Codes on fiscal transparency is discussed. Great strides have been made in coordinating preparation of the budgets of the central government and the noncommercial decentralized entities, and in timing their congressional presentation and approval to coincide. The new Organic Budget Law mandates the incorporation into the budget of all the self-generated revenues and the foreign grants received by central government institutions and deconcentrated entities.